Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Gamma plus or minus gamma-beta, two different outcomes?

  1. Mar 7, 2014 #1
    In Wikipedia it reads that γ(1+β) = [itex]\sqrt{\frac{1+β}{1-β}}[/itex], however, if I did my homework correctly I get γ(1+β) = [itex]\sqrt{\frac{1+β^{2}}{1-β^{2}}}[/itex]. Digging more deeply into why Wikipedia is listing it as such I found that it is based on the hyperbolic angles:γ=coshΘ. But it leads to definitions, not an explanation. More interestingly, WikiPedia is equating γ(1-β) with [itex]\sqrt{\frac{1-β}{1+β}}[/itex]. However, my calculations lead to

    γ(1-β) =γ-γβ=[itex]\sqrt{\frac{1}{1-β^{2}}}-\sqrt{\frac{β^{2}}{1-β^{2}}}=\sqrt{\frac{1-β^{2}}{1-β^{2}}}[/itex],

    which is equal to unity. I guess I am doing something utterly wrong and it feels like as if I have to start over learning calculus. I truly hope someone is setting me straight,

  2. jcsd
  3. Mar 7, 2014 #2


    Staff: Mentor

    \gamma = \frac{1}{\sqrt{1 - \beta^2}} = \frac{1}{\sqrt{\left( 1 - \beta \right) \left( 1 + \beta \right)}}

    \gamma \left( 1 + \beta \right) = \gamma \sqrt{\left( 1 + \beta \right) \left( 1 + \beta \right)} = \sqrt{\frac{\left( 1 + \beta \right) \left( 1 + \beta \right)}{\left( 1 - \beta \right) \left( 1 + \beta \right)}} = \sqrt{\frac{1 + \beta}{1 - \beta}}
  4. Mar 7, 2014 #3

    George Jones

    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    This is where a mistake is; look at what Peter wrote. I am not sure, but did you make the mistake

    $$\left( 1 + \beta \right)^2 = 1^2 + \beta^2?$$

    In general, ##\left( x + y\right)^2 = x^2 + 2xy + y^2 \ne x^2 + y^2##.

    Also, below, you seem to be saying ##\sqrt{x} - \sqrt{y} = \sqrt{x -y}##, which is not correct.

  5. Mar 7, 2014 #4


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    Transcribing into trigonometry...


    =\sqrt{\frac{ {(1+\tanh\theta)(1+\tanh\theta)}}{{(1-\tanh\theta)(1+\tanh\theta)}}}
    =\sqrt{\frac{ {1+\tanh\theta}}{{1-\tanh\theta}}}

    However, thinking trigonometrically...

    Strating from the LHS:

    Starting from the RHS:
    \sqrt{\frac{ {1+\tanh\theta}}{{1-\tanh\theta}}}
    =\sqrt{\frac{ 1+\frac{\sinh\theta}{\cosh\theta}}{{1-\frac{\sinh\theta}{\cosh\theta}}}}
    =\sqrt{\frac{ \cosh\theta+\sinh\theta}{\cosh\theta-\sinh\theta}}

  6. Mar 7, 2014 #5
    Try this:

    γ(1-β) =γ-γβ=[itex]\sqrt{\frac{1}{1-β^{2}}}-\sqrt{\frac{β^{2}}{1-β^{2}}}=\left(\frac{1}{\sqrt{1-β^2}}-\frac{β}{\sqrt{1-β^2}}\right)=\frac{(1-β)}{\sqrt{1-β^2}}=\frac{\sqrt{(1-β)(1-β)}}{\sqrt{(1-β)(1+β)}}=\frac{\sqrt{1-β}}{\sqrt{1+β}}[/itex]


    γ(1+β) =γ+γβ=[itex]\sqrt{\frac{1}{1-β^{2}}}+\sqrt{\frac{β^{2}}{1-β^{2}}}=\left(\frac{1}{\sqrt{1-β^2}}+\frac{β}{\sqrt{1-β^2}}\right)=\frac{(1+β)}{\sqrt{1-β^2}}=\frac{\sqrt{(1+β)(1+β)}}{\sqrt{(1-β)(1+β)}}=\frac{\sqrt{1+β}}{\sqrt{1-β}}[/itex]
  7. Mar 7, 2014 #6


    User Avatar
    Staff Emeritus
    Science Advisor

  8. Mar 8, 2014 #7
    I am grateful to all of you. Yes, I made a big mistake, thanks to using Microsoft Equation Editor, where I fooled myself. Always use pen and paper. This is not meant as an excuse, I stand corrected.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook